B Group Vitamins - Current Uses and Perspectives 2018
DOI: 10.5772/intechopen.79350
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Thiamine in Plants and Current Perspectives in Crop Improvement

Abstract: Current research is focusing on selecting potential genes that can alleviate stress and produce disease-tolerant crop variety. The novel paradigm is to investigate the potential of thiamine as a crop protection molecule in plants. Thiamine or vitamin B 1 is important for primary metabolism for all living organisms. The active form, thiamine pyrophosphate (TPP), is a cofactor for the enzymes involved in the synthesis of amino acids, tricarboxylic acid cycle and pentose phosphate pathway. Recently, thiamine is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 60 publications
1
20
2
Order By: Relevance
“…Thiamin is also known as a potent antioxidant and a crop protection molecule in plants, playing important roles in plant acclimation [17]. It has been shown that thiamin has the antioxidant capacity by O 2− /OH − scavenging and also recycling of vitamin C through the synthesis of NADPH [17,33]. Further, it has been revealed that paraquat-treated Arabidopsis, supplied by thiamin had reduced oxidative stress compounds, protein carbonyls, and dichlorofluorescein.…”
Section: The Role Of Thiamin In Mediating Plant Fitness and Acclimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiamin is also known as a potent antioxidant and a crop protection molecule in plants, playing important roles in plant acclimation [17]. It has been shown that thiamin has the antioxidant capacity by O 2− /OH − scavenging and also recycling of vitamin C through the synthesis of NADPH [17,33]. Further, it has been revealed that paraquat-treated Arabidopsis, supplied by thiamin had reduced oxidative stress compounds, protein carbonyls, and dichlorofluorescein.…”
Section: The Role Of Thiamin In Mediating Plant Fitness and Acclimationmentioning
confidence: 99%
“…Thiamin has also been shown to be involved in the acclimation responses to abiotic stresses and photoperiod [28][29][30][31][32]. It plays important roles, working directly as an antioxidant, scavenging ROS, and protection molecule, and indirectly by contributing to the cell energy poll, conferring the cell the necessary metabolic flexibility to acclimate to new conditions [17,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…These domains are well known for being involved in downstream signaling (i.e., mitogen-activated protein kinases) after pathogen recognition through either PTI or ETI (Jones & Dangl, 2006) We also found candidate genes with associated domains such as AP2, ubiquitin and patatine-like domains, as well as: plant auxin responsive proteins, glycosyl hydrolases proteins, superoxide dismutase, and others (Table 1). In general, these candidate genes are involved with the expression or synthesis of defense-related compounds, triggered by a possible Foph recognition through either PTI or ETI in P. peruviana as reported in other species (Dreher & Callis, 2007;Minic, 2008;Bielach, Hrtyan & Tognetti, 2017;Subki, Abidin & Yusof, 2018;Najafi, Sorkheh & Nasernakhaei, 2018;Cheng, Song & Wu, 2019).…”
Section: Discussionmentioning
confidence: 78%
“…Biosynthesis of aliphatic glucosinolates starts out from alanine, valine, and leucine, with the most abundant group of aliphatic glucosinolates synthesized from methionine [ 50 ]. This would explain the upregulation of branched-chain amino acids as well as the increase in B1 ( Figure 7 A), a vitamin that is involved in amino acid synthesis, pentose phosphate, and TCA cycle and is being increasingly recognized and linked with plant defense [ 51 , 52 ]. Moreover, this complements the observed enrichment of oxoacid Figure 7 A and Figure S6A ), which is linked with generalist herbivory, possibly through glucosinolates [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%